Spectrum resource allocation for wireless packet access with application to advanced cellular Internet service. - Chuang, J.C.-I (IEEE Journal on selected areas in communications)
The advanced cellular Internet service (ACIS) is targeted for applications such as Web browsing with a peak downlink transmission rate on the order of 1-2 Mbits/s using a wide-area cellular infrastructure. In order to provide bandwidth on demand using scarce radio spectrum, the medium-access control (MAC) protocol must: 1) handle dynamic and diverse traffic with high throughput, and 2) efficiently reuse limited spectrum with high peak rates and good quality. Most of the existing approaches do not sufficiently address the second aspect. This paper proposes a dynamic packet assignment (DPA) scheme which, without coordinating base stations, allocates spectrum on demand with no collisions and low interference to provide high downlink throughput. Interference sensing and priority ordering are employed to reduce interference probability. A staggered frame assignment schedule is also proposed to prevent adjacent base stations from allocating the same channel to multiple mobiles at the same time. Simulation results based on a packet data traffic model derived from wide-area network traffic statistics, which exhibit a ?self-similar? property when aggregating multiple sources, confirm that this method is able to reuse spectrum efficiently in a large cellular system having many users with short active periods. Distributed iterative power control further enhances spectrum efficiency such that the same channel can be simultaneously reused in every base station